2019
DOI: 10.1111/jcpt.13017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug‐related problems and subsequent clinical pharmacists’ interventions at a Swiss university hospital

Abstract: What is known and objective: The evaluation of clinical pharmacy services is essential for their further development and establishment. We analysed drug-related problems (DRPs) and subsequent clinical pharmacists' interventions (PIs) at a Swiss university hospital. Method:We conducted a retrospective analysis of DRPs and subsequent PIs that were identified and implemented during interdisciplinary ward rounds in internal medicine at the University Hospital Basel, Switzerland, between 2015 and 2017. We estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 29 publications
10
37
0
1
Order By: Relevance
“…(1) The incidence rates of interventions is 12.1 cases per 100 patient admissions, being similar to the rate of preventable ordering adverse drug events as 14.7 per 100 patients in previous report [10]. (2) ADE occurring (31.1%) was the most frequently detected DRPs and more than four fifths of DRPs were due to drug selection, dose selection and treatment duration, being in line with an evaluation of pharmacists' interventions in a Swiss study [8]. 3Drugs that most frequently caused DRPs during intervention were antibiotics, showing a similar composition but with a higher percentage than that of previous studies [8,31,32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…(1) The incidence rates of interventions is 12.1 cases per 100 patient admissions, being similar to the rate of preventable ordering adverse drug events as 14.7 per 100 patients in previous report [10]. (2) ADE occurring (31.1%) was the most frequently detected DRPs and more than four fifths of DRPs were due to drug selection, dose selection and treatment duration, being in line with an evaluation of pharmacists' interventions in a Swiss study [8]. 3Drugs that most frequently caused DRPs during intervention were antibiotics, showing a similar composition but with a higher percentage than that of previous studies [8,31,32].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that critical care pharmacists can play an essential role in promoting the delivery of pharmaceutical care (PC) and improve the overall quality of healthcare by offering individualized recommendations in complicated drug regimens, reducing the incidence rate of DRPs and decreasing preventable ADEs [6][7][8]. However, the development of PC in the ICU is currently facing three major challenges worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The incidence rates of interventions is 12.1 cases per 100 patient admissions, being similar to the rate of preventable ordering adverse drug events as 14.7 per 100 patients in previous report (Leape et al, 1999). (2) ADE occurring (31.1%) was the most frequently detected DRPs and more than four fifths of DRPs were due to drug selection, dose selection, and treatment duration, being in line with an evaluation of pharmacists' interventions in a Swiss study (Reinau et al, 2019). (3) Drugs that most frequently caused DRPs during intervention were antibiotics, showing a similar composition but with a higher percentage than that of previous studies (Klopotowska et al, 2010;Johansen et al, 2016;Reinau et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…ICU physicians might feel pressure when they held different opinions on treatment plans, and unnecessary medication orders could be carried out in this way. These situations bring great opportunities for pharmacists to get involved, communicate with both sides and ensure medication safety (Rudis and Brandl, 2000;Kane et al, 2003;Penm et al, 2014a;Tasaka et al, 2018;Reinau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation